Hindrances to Adoption of Artificial Insemination in Smallholder Dairy Farms at Chepkorio Division, Keiyo/Marakwet County, Kenya - J.K , Kitilit; R. J , Koech; S.A. , Amuti (African Journal of Education,Science and Technology (AJEST), 2015)
Kenya is an agricultural based economy with agricultural sector contributing about 25% of the gross domestic product (G.D.P). Dairy farming is an important part of this sector and contributes about 10% to the GDP. The industry has been growing at a rate of about 2.8 percent per annum which is double the rate of many African countries. The current study examined factors affecting the adoption of artificial insemination at Chepkorio Division and sought to determine the relationship between its adoption and milk yield. A questionnaire was developed and administered to forty five small scale dairy farmers in three villages using systematic sampling method. Results showed that the rate of adoption of artificial insemination (AI) was low at 12.5% while natural service was 47.5%, but 40% of the farmers practiced both AI and natural bull service on their farms. According to the findings of the current study, there was significant positive relationship between adoptions of AI technology and milk yield per animal. The study found that when all other factors are held constant, AI has a great impact on milk production where the F2 generation cow sired from AI gave up to 10.6 liters of milk daily compared to the same generation sired from the bulls whose milk yields was 4.15liters/cow/day.The factors hindering farmers from adopting AI included; availability of cheap bulls either from neighbours or their own, level of education of farmer, purpose of cattle, availability of AI technicians which was influenced by distance and road condition, land size and types of breeds of cattle kept. Dairy productivity in general was found to be low due to late maturity age for heifers, poor genetic potential, long calving interval and high economic loss due to disease incidences.